Sistem Informasi Keuangan pada SMA Swasta Daerah Kisaran Berbasis Mobile - Alda, Muhamad; Ulandari, Tri; Syahira, Jihan (MODELING: Jurnal Program Studi PGMI, 2023)
The purpose of writing this research is to analyze the weaknesses that exist in the system that is currently running at the SMA Swasta Daerah Kisaranin the payroll process. The process of recording and calculating salaries applied by this school is still conventional, causing the payroll process to be often late. With the new payroll information system, it will be very helpful in carrying out the process of calculating teacher salaries, attendance recap reports, as well as in making reports related to the payroll process. The research method used in the preparation of this research is to use research and development methods (Research and Development). Sistem Informasi Keungan Pada SMA Swasta Daerah Kisaran Berbasis Mobile in solving this problem, the authors designed an employee payroll information system.